Reproducibility in Psychological Science: When Do Psychological Phenomena Exist? - Iso-Ahola, Seppo E. (Frontiers in Psychology, 2017)
Scientific evidence has recently been used to assert that certain psychological phenomena do not exist. Such claims, however, cannot be made because (1) scientific method itself is seriously limited (i.e., it can never prove a negative); (2) non-existence of phenomena would require a complete absence of both logical (theoretical) and empirical support; even if empirical support is weak, logical and theoretical support can be strong; (3) statistical data are only one piece of evidence and cannot be used to reduce psychological phenomena to statistical phenomena; and (4) psychological phenomena vary across time, situations and persons. The human mind is unreproducible from one situation to another. Psychological phenomena are not particles that can decisively be tested and discovered. Therefore, a declaration that a phenomenon is not real is not only theoretically and empirically unjustified but runs counter to the propositional and provisional nature of scientific knowledge. There are only “temporary winners” and no “final truths” in scientific knowledge. Psychology is a science of subtleties in human affect, cognition and behavior. Its phenomena fluctuate with conditions and may sometimes be difficult to detect and reproduce empirically. When strictly applied, reproducibility is an overstated and even questionable concept in psychological science. Furthermore, statistical measures (e.g., effect size) are poor indicators of the theoretical importance and relevance of phenomena (cf. “deliberate practice” vs. “talent” in expert performance), not to mention whether phenomena are real or unreal. To better understand psychological phenomena, their theoretical and empirical properties should be examined via multiple parameters and criteria. Ten such parameters are suggested.